Coating composition, coating film, article, optical device, lighting device, air conditioner, and method for producing coating film
By using a coating composition with a specific particle size and content of silica particles, a suitable high boiling point solvent and water, the problem of whitening film is solved, and a coating film with high transparency and good light transmission performance is achieved.
Patent Information
- Application Number
- CN202080098360.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-04-08
AI Technical Summary
In the prior art, light scattering due to the concave and convex structure on the surface of the coating film causes whitening, which affects the light transmission performance and design aesthetics.
The coating composition containing silica fine particles having an average particle size of 3 nm or more and 25 nm or less, a high boiling point solvent having a boiling point of 150°C or more and 300°C or less, and a water content of silica fine particles is 0.1% by mass and 5. The content of high boiling point solvent is 20% by mass or more and 70% by mass or less.
It significantly improves the transparency of the coating film, inhibits light scattering, avoids whitening of the coating film, and maintains light transmission performance and design aesthetics.
Smart Images

Figure CN115298575B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a coating composition, a coating film, an article, an optical device, a lighting device, an air conditioner, and a method for producing the coating film, which contain silica fine particles. Background Art
[0002] Various dirt such as dust or oil smoke adheres to the surface of glass of buildings, lenses of outdoor cameras, and covers of lighting equipment. Various technologies for suppressing the adhesion of such dirt have been proposed. Patent document 1 discloses a technology for forming a coating film on the surface using a coating composition containing inorganic particle agglomerates and fluororesin particles that combine silica particles in a chain or beaded form. In the coating film, a large number of inorganic particle agglomerates exist on the surface side, and fluororesin particles also exist, thereby forming a concavo-convex structure on the surface of the coating film.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-89147 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, in the technology described in Patent Document 1, due to the concavo-convex structure existing on the surface of the coating film, light scattering occurs, so there is a problem that the coating film is slightly turbid. For example, if a slightly turbid coating film is formed on the surface of the lens of an outdoor camera, the light transmission performance of the lens is deteriorated, so it is not preferred. In addition, if a slightly turbid coating film is formed on the surface of the cover of a lighting device, the color tone of the base material changes, which impairs the design of the lighting device. Therefore, a coating film with higher transparency than before is required.
[0008] The present disclosure has been made in view of the above circumstances, and an object of the present invention is to obtain a coating composition capable of improving the transparency of a coating film compared with the related art.
[0009] Means for solving problems
[0010] In order to solve the above problems and achieve the purpose, the coating composition disclosed herein comprises: silica particles having an average particle size of 3 nm or more and 25 nm or less, a solvent having a boiling point of 150° C. or more and 300° C. or less, and water. The content of the silica particles is 0.1% by mass or more and 5% by mass or less. The content of the solvent is 20% by mass or more and 70% by mass or less.
[0011] Effects of the Invention
[0012] According to the present disclosure, the effect of improving the transparency of the coating film compared with the related art is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a cross-sectional view schematically showing an example of the structure of the coating film according to the first embodiment.
[0014] Figure 2 This is a cross-sectional view schematically showing an example of the method for producing a coating film according to the first embodiment.
[0015] Figure 3 This is a cross-sectional view schematically showing an example of the steps of the method for producing a coating film according to the first embodiment.
[0016] Figure 4 This is a cross-sectional view schematically showing an example of the steps of the method for producing a coating film according to the first embodiment.
[0017] Figure 5 This is a cross-sectional view schematically showing an example of the steps of the method for producing a coating film according to the first embodiment.
[0018] Figure 6 This is a front view showing an example of an optical device having a coating film according to the second embodiment.
[0019] Figure 7 yes Figure 6 VII-VII sectional view.
[0020] Figure 8 This is a front view showing an example of a lighting device having a coating film according to Embodiment 3.
[0021] Fig. 9 yes Figure 8 IX-IX sectional view.
[0022] Fig.10 This is a front view showing an example of an air conditioner having a coating film according to the fourth embodiment.
[0023] Fig.11 yes Fig.10 XI-XI sectional view.
[0024] Fig.12 This is a diagram summarizing the coating film formation conditions and evaluation results in Examples 1 to 17.
[0025] Fig.13 This is a diagram summarizing the coating film formation conditions and evaluation results in Comparative Examples 1-11. DETAILED DESCRIPTION
[0026] Hereinafter, a coating composition, a coating film, an article, an optical device, a lighting device, an air conditioner, and a method for producing a coating film according to embodiments of the present invention will be described in detail with reference to the drawings.
[0027] Implementation Method 1
[0028] <Coating composition>
[0029] The coating composition according to the first embodiment includes silica particles, a high boiling point solvent, and water. In addition, the coating composition according to the first embodiment may further include fluororesin particles and a non-volatile hydrophilic organic substance. The components included in the coating composition are described below.
[0030] <Silica particles>
[0031] The silica particles contained in the coating composition according to Embodiment 1 are components that become the main component of the coating film. By adding silica particles to the coating composition, a highly transparent hydrophilic surface can be formed in the coating film formed by the coating composition. Thus, the ability to suppress the adhesion of hydrophobic dirt can be improved, and the adhered water can be easily spread and easily flowed down.
[0032] Silica particles have a lower refractive index than other inorganic particles, and have a value close to the refractive index of transparent resins such as plastics and glass commonly used as substrates. If the refractive index of the substrate and the coating film is the same, the whitening due to light reflection at their interface and surface is suppressed, and the color tone of the substrate is not easily damaged.
[0033] The average particle size of the silica particles is preferably 3 nm or more and 25 nm or less, and particularly preferably 4 nm or more and 10 nm or less. Here, the average particle size refers to the value of the average particle size of the primary particles when measured by a laser scattering or dynamic scattering particle size distribution meter. In addition, the so-called primary particle is the smallest unit of the particle, which refers to the particle that is not further divided. The aggregate of primary particles in which multiple primary particles become one is called a secondary particle. If the average particle size of the silica particles is less than 3 nm, the coating becomes too dense, and the intermolecular force acting between the film surface and the dirt becomes larger, and sometimes the desired antifouling property cannot be obtained. If the average particle size of the silica particles is greater than 25 nm, the surface concavity of the coating becomes too large, and turbidity is easily generated. From the above, the average particle size of the silica particles is preferably 3 nm or more and 25 nm or less. In particular, when the average particle size of the silica particles is 4 nm or more and 10 nm or less, a coating with moderate density is formed, and the contact area between the surface of the coating and the dirt becomes smaller, so that sufficient antifouling property can be obtained. Here, the antifouling property refers to a property that dirt is difficult to adhere to or a property that adhered dirt can be easily removed.
[0034] With regard to the content of silica particles in the coating composition, it is preferably 0.1% by mass or more and 5% by mass or less, preferably 0.5% by mass or more and 2% by mass or less. When the content of the coating composition of silica particles is less than 0.1% by mass, the coating film formed becomes too thin, and sometimes the desired antifouling property cannot be obtained. On the other hand, when the content of the coating composition of silica particles is more than 5% by mass, the coating film becomes too thick, cracks and concavoconvex are generated, and sometimes it is easy to be turbid. From the above, the content of silica particles in the coating composition is preferably 0.1% by mass or more and 5% by mass or less. In particular, when the content of the coating composition of silica particles is 0.5% by mass or more and 2% by mass or less, a uniform coating film with appropriate thickness can be formed, and sufficient antifouling property can be obtained.
[0035] As for the silica particles with the above characteristics, they can be prepared according to known methods. For example, colloidal silica prepared from an aqueous solution of sodium silicate or prepared by a sol-gel method can be used as silica particles. As for silica particles, in addition to spherical shapes, they can also be hollow, flaky, rod-shaped and other irregular shapes. When flaky silica particles are used, there is a tendency for the obtained film strength to increase. Therefore, flaky silica particles are used in applications requiring wear resistance, thereby obtaining preferred results. It is also possible to achieve a balance between the strength of the transparent coating by mixing flaky silica particles and spherical silica particles. In addition, a product in which silica particles are connected into a rosary shape can also be used.
[0036] <High boiling point solvent>
[0037] The high boiling point solvent contained in the coating composition according to embodiment 1 is a solvent having a boiling point higher than normal temperature, and as described later, is a solvent having a boiling point of 150°C or more and 300°C or less. The high boiling point solvent controls the drying speed of the coating composition during the formation of the coating film. Thus, a liquid film can be formed while maintaining the initial concentration of the silica particles in the coating composition, and the agglomeration of the silica particles during the coating can be suppressed. Furthermore, by changing the content of the high boiling point solvent in a manner that prolongs the drying time, the liquid film after coating can be leveled. Through these effects, a uniform coating film can be obtained.
[0038] The boiling point of the high boiling point solvent is preferably 150°C or more and 300°C or less. If the boiling point of the high boiling point solvent is lower than 150°C, the drying speed becomes too fast, and the effect of preventing the aggregation of the silica particles and the leveling of the liquid film after coating cannot be obtained. On the other hand, if the boiling point of the high boiling point solvent exceeds 300°C, the solvent is likely to remain in the coating film, and a coating film with desired characteristics cannot be obtained. As described above, the boiling point of the high boiling point solvent is preferably 150°C or more and 300°C or less.
[0039] The solubility of the high boiling point solvent in water is not particularly limited, but is preferably 70% by mass or more. This is because if the solubility in water is less than 70% by mass, it is easy to separate from water.
[0040] As the high boiling point solvent, ethylene glycol, propylene glycol, ethylene glycol monomethyl ether acetate, ethyl lactate, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, dipropylene glycol monomethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol butyl methyl ether, tripropylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol monobutyl ether, ethylene glycol monophenyl ether, triethylene glycol monomethyl ether, diethylene glycol dibutyl ether, triethylene glycol butyl methyl ether, polyethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol monomethyl ether, N-methyl-2-pyrrolidone, etc. can be mentioned. In addition, they can be used alone or the product of two or more combinations can be used as the high boiling point solvent.
[0041] The content of the high boiling point solvent in the coating composition is more than 20 mass % and less than 70 mass %, preferably more than 30 mass % and less than 50 mass %. If the content of the high boiling point solvent is less than 20 mass %, the anti-agglomeration effect of the silicon dioxide particles and the leveling effect of the liquid film after coating cannot be fully obtained. In addition, when the content of the high boiling point solvent is more than 70 mass %, the solubility of the silicon dioxide particles in the coating composition and the fluororesin particles that can be arbitrarily included is reduced, and it is easy to condense. From the above, the content of the high boiling point solvent in the coating composition is preferably more than 20 mass % and less than 70 mass %. In particular, when the content of the high boiling point solvent in the coating composition is more than 30 mass % and less than 50 mass %, the leveling effect of the liquid film can be obtained while maintaining the dispersed state of the silicon dioxide particles and the fluororesin particles in the liquid film formed by the coating composition, so a uniform and transparent coating film can be formed.
[0042] <Water>
[0043] As the water included in the coating composition according to embodiment 1, it is not particularly limited, and tap water, pure water, RO (Reverse Osmosis) water, deionized water, etc. can be used. So-called RO water is water after impurities are removed from tap water using a reverse osmosis membrane. From the viewpoint of improving the dispersion stability of the silica particles in the coating composition, it is preferred that the calcium ions or magnesium ions contained in the water have few ionic impurities. Specifically, the ionic impurities of divalence or more contained in the water are preferably less than 200ppm, more preferably less than 50ppm. This is because, if the ionic impurities of divalence or more are more than 200ppm, agglomeration of silica particles occurs, and it is possible to produce a reduction in the coating property caused by the reduction in the fluidity of the coating composition and a reduction in the transparency of the coating film.
[0044] The content of water in the coating composition is not particularly limited, preferably more than 25 mass % and less than 80 mass %, more preferably more than 50 mass % and less than 70 mass %. If the content of water is less than 25 mass %, the solubility of the silicon dioxide particles in the coating composition and the fluororesin particles that can be optionally contained is reduced, and sometimes it is easy to condense. In addition, if the content of water is less than 25 mass %, the coating film thickens, and sometimes it is easy to produce defects such as cracks. On the other hand, if the content of water exceeds 80 mass %, the amount of the solid component in the composition is excessively reduced, and sometimes it is difficult to form a coating film efficiently. From the above, the content of water in the coating composition is preferably more than 25 mass % and less than 80 mass %. Especially, when the content of water in the coating composition is more than 50 mass % and less than 70 mass %, the dispersed state of silicon dioxide particles and fluororesin particles in the liquid film formed by the coating composition can be maintained, and a uniform and transparent coating film with appropriate thickness can be formed.
[0045] <Fluororesin particles>
[0046] The coating composition according to embodiment 1 may also contain fluororesin particles. By combining fluororesin particles, a hydrophobic surface can be formed locally on the formed coating. Thus, the ability to prevent dirt from adhering can be improved. In addition, lubricity can be imparted to the surface of the coating formed by the fluororesin particles. Thus, the wear resistance of the coating can be improved.
[0047] The fluororesin particles are not particularly limited, and examples thereof include particles formed from PTFE (polytetrafluoroethylene), FEP (tetrafluoroethylene-hexafluoropropylene copolymer), PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer), ETFE (ethylene-tetrafluoroethylene copolymer), ECTFE (ethylene-chlorotrifluoroethylene copolymer), PVDF (polyvinylidene fluoride), PCTFE (polychlorotrifluoroethylene), PVF (polyvinyl fluoride), vinyl fluoride-vinyl ether copolymer, vinyl fluoride-vinyl ester copolymer, copolymers and mixtures thereof, and products obtained by mixing other resins with these fluororesins.
[0048] The average particle size of the fluororesin particles is preferably 80 nm or more and 550 nm or less, more preferably 100 nm or more and 500 nm or less. When the average particle size of the fluororesin particles is less than 80 nm, it is sometimes impossible to fully form a hydrophobic portion on the surface of the coating. On the other hand, when the particle size of the fluororesin particles exceeds 550 nm, the surface concavity of the coating becomes larger, and dirt is easily caught, so the desired antifouling property is sometimes not obtained. In addition, due to the concavity of the surface of the coating, light scattering sometimes occurs, and the coating becomes turbid. From the above, the average particle size of the fluororesin particles is preferably 80 nm or more and 550 nm or less. In particular, when the average particle size of the fluororesin particles is 100 nm or more and 500 nm or less, a coating having a hydrophobic surface and appropriate concavity produced by the fluororesin particles is formed, so that sufficient antifouling property can be obtained.
[0049] In addition, the transparency of the coating film can be improved by minimizing the unevenness of the surface of the coating film formed by using rod-shaped or flaky fluororesin particles. Furthermore, the smoothness and transparency of the obtained film can be improved by using a dispersion of fluororesin particles containing low molecular weight components or solvents, which is flexible during coating and solidifies after volatilization of these components.
[0050] The fluororesin particles can be prepared by a known method. Fluororesin particles commercially available in a state of being dispersed in water can be used as a raw material of the coating composition.
[0051] With regard to the content of fluororesin particles in the coating composition, relative to the content of silica particles, it is preferably 5% by mass or more and 50% by mass or less, and particularly preferably 10% by mass or more and 30% by mass or less. If the content of fluororesin particles relative to the content of silica particles in the coating composition is less than 5% by mass, the ratio of the hydrophobic surface of the surface of the coating film is reduced, and sometimes the desired antifouling property cannot be obtained. On the other hand, if the content of fluororesin particles relative to the content of silica particles is more than 50% by mass, there is a tendency that dust is easily attached to the coating film, which is not preferred. From the above, the content of fluororesin particles relative to the content of silica particles in the coating composition is preferably 5% by mass or more and 50% by mass or less. In particular, when the content of fluororesin particles relative to the content of silica particles in the coating composition is 10% by mass or more and 30% by mass or less, a coating film having a hydrophilic surface and a hydrophobic surface in a moderate ratio is formed, so sufficient antifouling property can be obtained.
[0052] <Non-volatile hydrophilic organic matter>
[0053] In the coating composition according to the first embodiment, a non-volatile hydrophilic organic substance as a non-volatile and hydrophilic organic substance may also be included. By matching the non-volatile hydrophilic organic substance, the gaps in the formed coating film can be filled, the internal scattering of the coating film can be reduced, and the transparency of the coating film can be improved. In addition, the coating property of the coating composition can be improved.
[0054] The nonvolatile hydrophilic organic material is not particularly limited, and various organic materials that are not deliquescent and nonvolatile can be used. Examples of the nonvolatile hydrophilic organic material include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, dimethicone copolyol, and mixtures thereof.
[0055] As a non-volatile hydrophilic organic substance, a surfactant can also be used. As the surfactant, there is no particular limitation, and a nonionic surfactant that is not easy to cause aggregation of silica particles is preferred. However, if attention is paid to the amount added, the pH of the solvent, etc., anionic surfactants and cationic surfactants can also be used.
[0056] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, polyoxyethylene alkylamines, polyoxyethylene alkylamides, sorbitan alkyl esters and polyoxyethylene sorbitan alkyl esters.
[0057] Examples of the anionic surfactant include higher alcohol sulfates (Na salts or amine salts), alkyl allyl sulfonates (Na salts or amine salts), alkyl naphthalene sulfonates (Na salts or amine salts), alkyl naphthalene sulfonate condensates, alkyl phosphates, dialkyl sulfosuccinates, rosin soaps, fatty acid salts (Na salts or amine salts), and the like.
[0058] Examples of the cationic surfactant include octadecylamine acetate, imidazoline derivative acetate, polyalkylene polyamine derivatives or salts thereof, octadecyltrimethylammonium chloride, triethylaminoethylalkylamide halide, alkylpyridinium sulfate and alkyltrimethylammonium halide.
[0059] There is no particular limitation on the non-volatile hydrophilic organic matter, and a non-volatile hydrophilic organic matter having an average molecular weight of more than 400 and less than 500,000 can be used, preferably a non-volatile hydrophilic organic matter having an average molecular weight of more than 700 and less than 100,000. When the average molecular weight is lower than 400, when the amount of the non-volatile hydrophilic organic matter added is large, the adhesion of dust sometimes increases, which is not preferred. In addition, when the average molecular weight exceeds 500,000, the fluidity of the coating composition decreases, and sometimes homogeneous coating becomes difficult. From the above, the average molecular weight of the non-volatile hydrophilic organic matter is preferably more than 400 and less than 500,000. In particular, when the average molecular weight of the non-volatile hydrophilic organic matter is more than 700 and less than 100,000, due to moderate fluidity, a coating film with high transparency that fills the voids of the coating film can be obtained.
[0060] With regard to the content of non-volatile hydrophilic organic matter in the coating composition, relative to the content of silicon dioxide particles, it is preferably more than 10 mass % and less than 40 mass %, and particularly preferably more than 10 mass % and less than 30 mass %. If the content of the non-volatile hydrophilic organic matter relative to the content of the silicon dioxide particles in the coating composition is less than 10 mass %, sometimes the internal voids of the formed coating film cannot be fully buried, or sometimes the expansibility of the coating composition is reduced, and sometimes the transparency of the coating film becomes insufficient. On the other hand, if the content of the non-volatile hydrophilic organic matter relative to the content of the silicon dioxide particles is more than 40 mass %, the coating film is excessively softened, and sometimes the durability becomes insufficient. From the above, the content of the non-volatile hydrophilic organic matter relative to the content of the silicon dioxide particles in the coating composition is preferably more than 10 mass % and less than 40 mass %. In particular, when the content of the nonvolatile hydrophilic organic substance in the coating composition is 10% by mass or more and 30% by mass or less, the effect of sufficiently filling the voids in the coating film is obtained, so that a coating film with high transparency can be formed.
[0061] <Other>
[0062] As for the coating composition according to Embodiment 1, in the range that does not hinder the effect of the present disclosure, from the viewpoint of imparting various characteristics to the coating composition, it is possible to include components known in the technical field. As examples of such components, coupling agents, silane compounds, etc. can be cited. As for the amount of these components, as long as it is not particularly limited to the range that does not hinder the effect of the present disclosure, it can be appropriately adjusted according to the type of the components used.
[0063] The method for producing the coating composition according to the first embodiment containing the above-mentioned components is not particularly limited, and can be carried out according to a method known in the relevant technical field. Specifically, the coating composition can be prepared by blending the above-mentioned components and mixing and stirring them.
[0064] Next, the coating film produced using the above-mentioned coating composition will be described.
[0065] <Coating>
[0066] The coating composition according to Embodiment 1 is applied onto a substrate and dried to form a coating film.
[0067] Figure 1 It is a cross-sectional view schematically showing an example of the structure of the coating film according to Embodiment 1. It is to be explained that here, the case where the coating composition contains silica particles, a high boiling point solvent, water, fluororesin particles and a non-volatile hydrophilic organic matter is taken as an example. The coating film 10 has: a silica particle layer 11 arranged on a substrate 20 and formed by agglomeration of silica particles; and fluororesin particles 12 arranged in a state of being dispersed in the silica particle layer 11. The fluororesin particles 12 include particles exposed on the surface of the coating film 10, that is, the surface of the silica particle layer 11, and particles not exposed. That is, the fluororesin particles 12 are arranged in a state of being partially exposed on the surface of the coating film 10 and dispersed in the silica particle layer 11.
[0068] exist Figure 1 In the figure, cracks 13 are schematically shown as an example of defects formed by the aggregation of silica particles when the liquid film of the applied coating composition is dried. In fact, in many cases, it is not clear cracks 13, but small gaps are formed. In the past, these defects caused light scattering and became the cause of the turbidity of the film. However, in the coating film 10 according to embodiment 1, a state is formed in which the inside of these defects is filled with non-volatile hydrophilic organic matter 14. As a result, light scattering is suppressed and the transparency of the coating film 10 is increased. In addition, by adding the non-volatile hydrophilic organic matter 14, the effect of suppressing the generation of these defects itself is also obtained.
[0069] like Figure 1As shown in , the surface of the coating film 10 according to the first embodiment includes both a hydrophilic portion derived from the silica fine particles and a hydrophobic portion derived from the fluororesin particles 12 .
[0070] In addition, as described later, the coating composition according to the first embodiment contains a high boiling point solvent, so the time from coating the coating composition on the substrate 20 to form a liquid film to drying to form the coating film 10 is longer than before. Therefore, the liquid film after coating is leveled, and the coating film 10 is formed in this state. As a result, the coating film 10 with smoothed surface irregularities is obtained, and the transparency can be improved compared with the past.
[0071] The film thickness of the coating 10 is preferably more than 20nm and less than 250nm. If the film thickness is thinner than 20nm, the coating 10 is too thin and the desired antifouling property cannot be obtained. In addition, if the film thickness is thicker than 250nm, the surface concavoconvexity of the coating 10 becomes larger, and sometimes white turbidity occurs. From the above, the film thickness of the coating 10 is preferably more than 20nm and less than 250nm. In addition, when the film thickness of the coating 10 is more than 80nm and less than 150nm, particularly when it is about 100nm, the coating 10 can be given an antireflection function, and the transmittance of the substrate 20 coated with the coating 10 can be improved.
[0072] <Base material>
[0073] The substrate is a component that becomes the object of film formation. In one example, the substrate is a component that constitutes an article. In addition, as the substrate, transparent glass or transparent plastic can be used. In the case of a transparent substrate forming a film, in addition to not deteriorating the transparency of the substrate, an anti-reflection effect is obtained by appropriately designing the film thickness of the film, and the light transmittance can be improved. In addition, in the case of a non-transparent substrate forming a film, there is an advantage that a treatment can be performed without changing the color tone of the substrate. In the case of a glossy surface, the above-mentioned anti-reflection effect also obtains an effect of improving the depth or vividness of the color.
[0074] <Manufacturing method>
[0075] Figure 2 : is a cross-sectional view schematically showing an example of a method for manufacturing a coating film according to Embodiment 1. A cloth-like object 31 impregnated with a coating composition is fixed to a block 30 as a coating machine, and the surface to which the cloth-like object 31 is fixed is brought into close contact with a substrate 20 and slides, thereby applying the coating composition to the substrate 20. Thus, a liquid film composed of the coating composition is formed on the substrate 20. By combining the cloth-like object 31 and the block 30, a small amount of the coating composition can be applied to the substrate 20 while applying uniform pressure to the cloth-like object 31, and a uniform coating film can be formed.
[0076] The thickness of the cloth 31 is preferably 5 mm or less. This is because if it is thicker than 5 mm, the impregnation amount of the coating composition increases excessively, so it is sometimes not possible to apply it evenly. Here, the cloth 31 refers to a material formed by gathering fibers such as woven fabrics, non-woven fabrics, and paper. There is no particular limitation on the raw material of the cloth 31 as long as it can be impregnated with the coating composition. An example of the cloth 31 is a cloth made of rayon. It should be noted that if fiber scraps are generated, it will become a defect of the coating, so it is preferably free of short fibers as much as possible.
[0077] The shape of the block 30 is not particularly limited, but is preferably a shape that can slide along the surface of the substrate 20. That is, the block 30 having a surface that follows the shape of the surface of the substrate 20 is preferably used.
[0078] There is no particular limitation on the material of the block 30. In one example, the material of the block 30 is polycarbonate. In addition, as the material of the block 30, a material that can be impregnated with a coating composition can also be used. Sponges of various materials having interconnecting pores can be used as the block 30, and the pore diameter of the sponge is preferably greater than 0.05 mm and less than 2 mm, and more preferably greater than 0.1 mm and less than 1.5 mm. When the pore diameter is less than 0.05 mm, it is difficult to apply sufficient coating composition. In addition, when the pore diameter exceeds 2 mm, the coating amount of the coating composition becomes too much, and the liquid film is prone to unevenness, so it is not preferred. From the above, the pore diameter of the sponge is preferably greater than 0.05 mm and less than 2 mm.
[0079] The coating method described above is a method for stably coating on a large area. As a coating method, in addition, dipping, a coating method using a brush, a spraying method, a coating method using various coating machines, etc. can also be used. In addition, the coating composition can also be cast on the substrate 20 and coated.
[0080] Figures 3 to 5 1 is a cross-sectional view schematically showing an example of the steps of the method for producing a coating film according to Embodiment 1. First, a liquid film forming step is performed in which a coating composition is applied on a substrate to form a liquid film. Figure 3 In Figure 2 The initial state of the liquid film 10A immediately after the coating composition is applied to the substrate 20. Figure 3 As shown in FIG. 1 , in the initial state, the thickness of the liquid film 10A formed by the applied coating composition is uneven. In addition, in the liquid film 10A, the silicon dioxide particles 15 are dispersed in the solvent 16 without aggregation. Next, a drying step is performed to dry the liquid film 10A in this state.
[0081] In the coating composition according to the first embodiment, since the high boiling point solvent is contained, the solvent 16 in the coating composition does not evaporate immediately after coating, but takes a time corresponding to the content of the high boiling point solvent for the solvent 16 to evaporate. Figure 4 As shown in , the liquid film 10A is gradually leveled, and thus the upper surface of the liquid film 10A becomes flat. In addition, at this time, the silica particles 15 do not aggregate in the liquid film 10A and remain dispersed.
[0082] Afterwards, if the final solvent 16 is dried, then Figure 5 As shown in FIG. 1 , the silica fine particles 15 are aggregated to form a coating film 10 having a silica fine particle layer 11 .
[0083] As a method for drying the coating composition, it is important not to cause temperature unevenness on the surface of the coated liquid film 10A. After coating, it is preferably allowed to dry naturally. When airflow is used to accelerate the drying, it is preferably not to use a high-temperature airflow that is 15°C or higher than the temperature of the substrate 20. When a high-temperature airflow that is 15°C or higher than the temperature of the substrate 20 is used, temperature unevenness occurs on the surface of the coated liquid film 10A, and the coating 10 obtained after drying also becomes uneven. The speed of the airflow is not particularly limited, but is preferably 25m / sec or less. This is because: if the speed of the airflow exceeds 25m / sec, the liquid film 10A before drying is disturbed, and sometimes a uniform coating 10 cannot be obtained.
[0084] In embodiment 1, the coating composition is made to include silica particles, a high boiling point solvent and water. The average particle size of the silica particles is 3 nm or more and 25 nm or less, and the content of the silica particles in the coating composition is 0.1 mass % or more and 5 mass % or less. In addition, the boiling point of the high boiling point solvent is 150 ° C or more and 300 ° C or less, and the content of the high boiling point solvent in the coating composition is 20 mass % or more and 70 mass % or less. Thus, when the coating composition is applied to the substrate, compared with the previous situation with a high boiling point solvent having less content than the above-mentioned high boiling point solvent, the drying speed of the liquid film coated with the coating composition slows down, and the liquid film is leveled until the solvent in the liquid film is dried. The liquid film in the leveled state is dried to obtain a coating film with uniform thickness. In the coating film, the concavo-convex structure on the surface is suppressed, so the light scattering caused by the concavo-convex structure is also suppressed. As a result, it has the effect of being able to form a coating film with higher transparency than in the past.
[0085] Implementation Method 2
[0086] In Embodiment 2, a case where the coating film described in Embodiment 1 is formed on an optical device as an article will be described. Figure 6 is a front view showing an example of an optical device having a coating film according to Embodiment 2, Figure 7 yes Figure 6 VII-VII cross-sectional view. In Embodiment 2, a camera 100 is cited as an example of an optical device. The camera 100 includes a camera body 111 and a lens 112 in a housing 110. When the camera 100 is used indoors or outdoors, dirt may adhere to the surface of the lens 112. Therefore, by forming the coating film 10 described in Embodiment 1 on the surface of the lens 112, it is possible to prevent the adhesion of dirt for a long time without affecting the image captured by the camera 100.
[0087] In the second embodiment, the coating film 10 is formed on the lens 112 of the camera 100. Since the coating film 10 has higher transparency than before, it is expected that the light focusing performance of the lens 112 will be the same as that before the coating film 10 is applied. In addition, by adjusting the film thickness of the coating film 10 so as to have an anti-reflection function, the transmittance of the lens 112 coated with the coating film 10 can also be improved.
[0088] Implementation 3
[0089] In Embodiment 3, a case where the coating film described in Embodiment 1 is formed on a lighting device as an article will be described. Figure 8 is a front view showing an example of a lighting device having a coating film according to Embodiment 3, Fig. 9 yes Figure 8 IX-IX cross-sectional view. In Embodiment 3, the lighting device 200 includes: a main body 210 that radiates light, and a lighting cover 211 that covers the main body 210. When the lighting device 200 is used indoors or outdoors, dirt sometimes adheres to the surface of the lighting cover 211. Therefore, by forming the coating film 10 described in Embodiment 1 on the surface of the lighting cover 211, it is possible to prevent the adhesion of dirt for a long time without affecting the illumination.
[0090] In Embodiment 3, the coating film 10 is formed on the lighting cover 211 of the lighting device 200. Since the coating film 10 has higher transparency than before, the light transmission performance of the lighting cover 211 equivalent to that before the coating film 10 is applied can be expected.
[0091] Implementation 4
[0092] In the fourth embodiment, a case where the coating film described in the first embodiment is formed on an air conditioner as an article will be described. Fig.10 is a front view showing an example of an air conditioner having a coating film according to Embodiment 4, Fig.11 yes Fig.10XI-XI cross-sectional view. In Embodiment 4, the air conditioner 300 is installed indoors in one example, and is a device that sucks in outdoor air to supply air to the room, and exhausts indoor air to the outside. The air conditioner 300 includes: a shell 310 that covers a main body (not shown) that supplies and exhausts air to the room. When the air conditioner 300 is used indoors, dirt sometimes adheres to the surface of the shell 310. Therefore, by forming the coating film 10 described in Embodiment 1 on the surface of the shell 310, it is possible to prevent the adhesion of dirt for a long time without changing the appearance of the product.
[0093] In Embodiment 4, the coating film 10 is formed on the housing 310 of the air conditioner 300. Since the coating film 10 has higher transparency than before, the color tone of the housing 310 can be maintained to be the same as that before the coating film 10 is applied.
[0094] Example
[0095] Hereinafter, the details of the present disclosure will be described with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples and Comparative Examples.
[0096] <Method for preparing coating composition and method for forming coating film>
[0097] [Example 1]
[0098] Colloidal silica (ST-O manufactured by Nissan Chemical Industries, Ltd.) containing silica fine particles having an average particle diameter of 12 nm, diethylene glycol monobutyl ether having a boiling point of 230° C. as a high boiling point solvent, and deionized water as water were mixed and stirred to prepare a coating composition. In the coating composition, the content of the silica fine particles was 1% by mass, the content of the diethylene glycol monobutyl ether was 50% by mass, and the content of the deionized water was the balance.
[0099] The obtained coating composition was impregnated into a nonwoven fabric (manufactured by Kuraray Kuraflex Co., Ltd., product name: Kurarayon (registered trademark) wiper, fiber used: rayon) and fixed to a block made of polycarbonate. The nonwoven fabric surface was brought into close contact with a glass substrate (50 mm×50 mm×1 mm) and slid, and then dried at 25°C for 24 hours to form a coating film.
[0100] [Example 2]
[0101] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 20% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0102] [Example 3]
[0103] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 21% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0104] [Example 4]
[0105] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 55% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0106] [Example 5]
[0107] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 69 mass %. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0108] [Example 6]
[0109] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 70% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0110] [Example 7]
[0111] A coating composition was prepared in the same manner as in Example 1 except that dipropylene glycol dimethyl ether having a boiling point of 171° C. was used instead of diethylene glycol monobutyl ether as a high boiling point solvent. Also, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0112] [Example 8]
[0113] A coating composition was prepared in the same manner as in Example 1 except that the content of the silica fine particles was changed to 0.2 mass %. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0114] [Example 9]
[0115] A coating composition was prepared in the same manner as in Example 1 except that the content of the silica fine particles was changed to 4% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0116] [Example 10]
[0117] A coating composition was prepared in the same manner as in Example 1 except that the average particle size of the silica fine particles was changed to 5 nm. Also, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0118] [Example 11]
[0119] A coating composition was prepared in the same manner as in Example 1 except that the average particle size of the silica fine particles was changed to 20 nm. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0120] [Example 12]
[0121] A coating composition was prepared in the same manner as in Example 1 except that 10% by mass of PTFE particles (manufactured by Mitsui Dupont Fluoro Chemical Co., Ltd., product name: 31JR) were added as fluororesin particles relative to the silica particles. The average particle size of the PTFE particles was 0.25 μm. In addition, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0122] [Example 13]
[0123] A coating composition was prepared in the same manner as in Example 1 except that 40% by mass of PTFE particles (manufactured by Mitsui Dupont Fluoro Chemical Co., Ltd., product name: 31JR) were added as fluororesin particles relative to the silica particles. The average particle size of the PTFE particles was 0.25 μm. In addition, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0124] [Example 14]
[0125] A coating composition was prepared in the same manner as in Example 1 except that 15% by mass of polyethylene glycol (manufactured by Tokyo Chemical Industry Co., Ltd., product name: polyethylene glycol 400) was added as a nonvolatile hydrophilic organic substance relative to the silica fine particles. The average molecular weight of the polyethylene glycol was 380 to 420. In addition, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0126] [Example 15]
[0127] A coating composition was prepared in the same manner as in Example 1 except that 35% by mass of polyethylene glycol (manufactured by Tokyo Chemical Industry Co., Ltd., product name: polyethylene glycol 400) was added as a nonvolatile hydrophilic organic substance relative to the silica fine particles. The average molecular weight of the polyethylene glycol was 380 to 420. In addition, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0128] [Example 16]
[0129] A coating film was formed in the same manner as in Example 1 except that the coating composition of Example 1 was applied to an acrylic substrate (ABS (acrylonitrile-butadiene-styrene), 50 mm×50 mm×2 mm).
[0130] [Example 17]
[0131] The coating composition of Example 1 was spray-coated on a glass substrate (50 mm×50 mm×1 mm), and then dried at 25° C. for 24 hours to form a coating film.
[0132] [Comparative Example 1]
[0133] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 15% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0134] [Comparative Example 2]
[0135] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 19% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0136] [Comparative Example 3]
[0137] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 71% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0138] [Comparative Example 4]
[0139] A coating composition was prepared in the same manner as in Example 1 except that the content of diethylene glycol monobutyl ether as the high boiling point solvent was changed to 75% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0140] [Comparative Example 5]
[0141] A coating composition was prepared in the same manner as in Example 1 except that ethanol having a boiling point of 87° C. was used instead of diethylene glycol monobutyl ether as a high boiling point solvent. Also, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0142] [Comparative Example 6]
[0143] A coating composition was prepared in the same manner as in Example 1 except that lithium silicate (manufactured by Nissan Chemical Industries, Ltd., product name: Lithium Silicate 45) was used instead of the silica fine particles. Also, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0144] [Comparative Example 7]
[0145] A coating composition was prepared in the same manner as in Example 1 except that the average particle size of the silica fine particles was changed to 30 nm. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0146] [Comparative Example 8]
[0147] A coating composition was prepared in the same manner as in Example 1 except that the content of the silica fine particles was changed to 0.05 mass %. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0148] [Comparative Example 9]
[0149] A coating composition was prepared in the same manner as in Example 1 except that the content of the silica fine particles was changed to 7% by mass. Also, in the same manner as in Example 1, a coating film was formed on a glass substrate.
[0150] [Comparative Example 10]
[0151] A coating composition was prepared in the same manner as in Example 1 except that 60% by mass of PTFE particles (manufactured by Mitsui Dupont Fluoro Chemical Co., Ltd., product name: 31JR) were added as fluororesin particles relative to the silica particles. The average particle size of the PTFE particles was 0.25 μm. In addition, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0152] [Comparative Example 11]
[0153] A coating composition was prepared in the same manner as in Example 1 except that 50% by mass of polyethylene glycol (manufactured by Tokyo Chemical Industry Co., Ltd., product name: polyethylene glycol 400) as a nonvolatile hydrophilic organic substance was added to the silica fine particles. The average molecular weight of the polyethylene glycol was 380 to 420. In addition, a coating film was formed on a glass substrate in the same manner as in Example 1.
[0154] <Evaluation method of coating film>
[0155] The coating films formed from the coating compositions of Examples 1 to 15 and Comparative Examples 1 to 11 and the coating films formed from the coating compositions of Examples 16 and 17 were measured for film thickness, and further evaluated for transparency and antifouling properties.
[0156] Determination of film thickness
[0157] The coating film formed on the substrate was partially cut and the step height difference between the coating film and the substrate was measured using a 3D measurement laser microscope (manufactured by Olympus Corporation) to measure the film thickness. The measurement results of the coating film thickness were classified according to the following criteria.
[0158] 1: Film thickness less than 20nm
[0159] 2: Film thickness is 20nm or more and 120nm or less
[0160] 3: Film thickness exceeding 120nm and less than 250nm
[0161] 4: Film thickness exceeds 250nm
[0162] Transparency evaluation
[0163] The haze of the coating film was measured using a haze garden (manufactured by BYK-Gardner). The measurement result of the haze of the coating film was evaluated according to the following criteria, and when the haze was less than 4%, it was judged that the transparency was high.
[0164] 1: Haze less than 2%
[0165] 2: Haze is 2% or more and less than 3%
[0166] 3: Haze is 3% or more and less than 4%
[0167] 4: Haze is 4% or more
[0168] Evaluation of antifouling properties
[0169] As the antifouling performance, the adhesion of sand and dust, which is a hydrophilic fouling substance, to the coating film was evaluated. Specifically, under the conditions of a temperature of 25°C and a humidity of 50%, a JIS (Japanese Industrial Standards) test powder, namely Kanto loam dust, with a central particle size in the range of 1 μm or more and 3 μm or less was sprayed onto the coating film with air. Afterwards, the Kanto loam dust sprayed on the coating film was transferred to a repair tape (manufactured by Sumitomo 3M Co., Ltd.). In another transparent substrate to which the tape with the transferred dust was attached, the absorbance at a wavelength of 550 nm was measured by a spectrophotometer (manufactured by Shimadzu Corporation, product name: UV-3100PC). The absorbance is evaluated according to the following criteria. If the absorbance is less than 0.3, it is judged to have high antifouling properties.
[0170] 1: Absorbance less than 0.1
[0171] 2: Absorbance is 0.1 or more and less than 0.2
[0172] 3: Absorbance is 0.2 or more and less than 0.3
[0173] 4: Absorbance is 0.3 or above
[0174] Fig.12 This is a graph summarizing the coating film formation conditions and evaluation results in Examples 1 to 17. Fig.13 This is a diagram summarizing the coating film formation conditions and evaluation results in Comparative Examples 1 to 11.
[0175] like Fig.12As shown in, the average particle size of the silica particles of the coating compositions of Examples 1 to 11 is in the range of 3 nm to 25 nm, and the content of the silica particles in the coating compositions is in the range of 0.1 mass % to 5 mass %. In addition, the boiling point of the high boiling point solvent of the coating compositions of Examples 1-11 is in the range of 150°C to 300°C, and the content of the high boiling point solvent in the coating compositions is in the range of 20 mass % to 70 mass %. Therefore, the coating films formed using these coating compositions have good antifouling properties and good transparency. In addition, in the coating compositions of Examples 12 and 13, fluororesin particles are contained in the range of 5 mass % to 50 mass % relative to the silica particles, so the antifouling properties and transparency are good. Similarly, in the coating compositions of Examples 14 and 15, since non-volatile hydrophilic organic matter is contained in the range of 10 mass % to 40 mass % relative to the content of non-volatile hydrophilic organic matter of silica particles, the antifouling properties and transparency are good.
[0176] The coating film formed on the acrylic substrate in Example 16 and the coating film formed by spraying in Example 17 also had good antifouling properties and transparency. That is, when the substrate is glass or acrylic, the coating film has good antifouling properties and transparency. Whether the coating film is formed by coating using a non-woven fabric or the coating film is formed by spraying, the antifouling properties and transparency are good.
[0177] In contrast, Fig.13 As shown in the figure, in Comparative Examples 1 and 2, the transparency was evaluated low. It is believed that this is because the amount of high boiling point solvent added was insufficient, so the effect of forming a uniform film could not be fully obtained. In Comparative Examples 3 and 4, the transparency, i.e., the antifouling property was evaluated low. It is believed that this is because the amount of high boiling point solvent added was excessive, so the dispersibility of the silica particles was reduced, and the surface unevenness of the coating film became larger.
[0178] In Comparative Example 5, the transparency was evaluated low. This is considered to be because the boiling point of ethanol used as a solvent is 87°C, which is lower than the boiling points of other high-boiling-point solvents. It should be noted that a solvent with a boiling point of 171°C was used in Example 7, so it is considered that a coating film with excellent antifouling properties and transparency can be obtained if the boiling point of the high-boiling-point solvent is 150°C or higher. In addition, if the boiling point exceeds 300°C, the solvent is likely to remain in the coating film, so it is considered that it is preferable to use a high-boiling-point solvent with a boiling point of 300°C or less.
[0179] In Comparative Examples 6 to 9, the transparency or antifouling property was evaluated low. This is considered to be because the average particle size of the silica fine particles was too large or the amount of silica fine particles added was too small or too large.
[0180] In Comparative Example 10, the transparency was evaluated low. This is considered to be due to the excessive addition of fluororesin particles, so dust is easily attached. It should be noted that in Example 13, if the content of fluororesin particles relative to silica particles is 40% by mass, it is considered that the addition amount of fluororesin particles is preferably 50% by mass or less.
[0181] In Comparative Example 11, the antifouling property was evaluated low. This is considered to be because the coating film became too soft due to the excessive addition amount of the nonvolatile hydrophilic organic substance.
[0182] <Examples of using the coating composition in articles>
[0183] [Example 18]
[0184] The coating composition of Example 1 was sprayed on the outer side of a glass lens of an outdoor camera, and then naturally dried at 25°C for 24 hours.
[0185] [Example 19]
[0186] The coating composition of Example 1 was impregnated into a nonwoven fabric (manufactured by Kuraray Kuraflex Co., Ltd., product name: Kuraray Wiper, fiber used: rayon) and fixed to a block made of polycarbonate. The nonwoven fabric surface was brought into close contact with an acrylic cover of a lighting device and slid, and then naturally dried at 25°C for 24 hours to form a coating film.
[0187] [Example 20]
[0188] The coating composition of Example 1 was impregnated into a nonwoven fabric (manufactured by Kuraray Kuraflex Co., Ltd., product name: Kuraray Wiper, fiber used: rayon) and fixed to a block made of polycarbonate. The nonwoven fabric surface was brought into close contact with the outer surface of the housing of an indoor air conditioner and slid, and then naturally dried at 25°C for 24 hours to form a coating film.
[0189] In Examples 18-20, the coating film was formed on each substrate, and the appearance of the substrate did not change. That is, the coating film formed in Examples 18-20 has high transparency. In addition, under the conditions of temperature 25°C and humidity 50%, after air was sprayed with JIS test powder, i.e., Kanto loam dust, with a central particle size in the range of 1 μm or more and 3 μm or less, each object was slightly vibrated. As a result, it can be seen that in each object formed with the coating film of Examples 18-20, the dust fell, so the coating film formed in Examples 18-20 has high antifouling properties.
[0190] The configurations shown in the above embodiments are merely examples, and may be combined with other known techniques, the embodiments may be combined with each other, and part of the configuration may be omitted or changed without departing from the gist of the invention.
[0191] Description of Reference Numerals
[0192] 10 coating film, 10A liquid film, 11 silica particle layer, 12 fluororesin particles, 13 cracks, 14 non-volatile hydrophilic organic matter, 15 silica particles, 16 solvent, 20 substrate, 30 block, 31 cloth-like object, 100 camera, 110, 310 housing, 111 camera body, 112 lens, 200 lighting equipment, 210 body, 211 lighting cover, 300 air conditioner.
Claims
1. A coating composition, characterized in that Include: Silica fine particles having an average particle size of 3 nm or more and 25 nm or less, A solvent having a boiling point of 150°C or higher and 300°C or lower, and water, The content of the silicon dioxide fine particles is 0.1 mass % or more and 5 mass % or less, The content of the solvent is 20% by mass or more and 70% by mass or less.
2. The coating composition according to claim 1, characterized in that The present invention further comprises fluororesin particles, wherein the content of the fluororesin particles is 5 mass % or more and 50 mass % or less based on the silica fine particles.
3. The coating composition according to claim 1 or 2, characterized in that The silica fine particles further contain a nonvolatile hydrophilic organic substance which is a nonvolatile and hydrophilic organic substance, wherein the content of the nonvolatile hydrophilic organic substance is 10 mass % or more and 40 mass % or less relative to the silica fine particles.
4. A coating film formed on a substrate by the coating composition according to claim 1, characterized in that: The present invention comprises: a silica fine particle layer which is disposed on the substrate and formed by agglomerating the silica fine particles.
5. A coating film formed on a substrate by the coating composition according to claim 2, characterized in that: The method comprises: a silica fine particle layer which is arranged on the substrate and formed by agglomerating the silica fine particles; The fluororesin particles are partially exposed on the surface of the coating film and are arranged in a state of being dispersed in the silica fine particle layer.
6. A coating film formed on a substrate by the coating composition according to claim 3, characterized in that: The method comprises: a silica fine particle layer which is arranged on the substrate and formed by agglomerating the silica fine particles; The nonvolatile hydrophilic organic matter fills defects in the silica fine particle layer.
7. The coating according to any one of claims 4 to 6, characterized in that: The film thickness is greater than or equal to 20 nm and less than or equal to 250 nm.
8. The coating according to any one of claims 4 to 7, characterized in that: The substrate is glass or transparent resin.
9. An article, characterized in that A coating film according to any one of claims 4 to 8.
10. An optical device comprising a lens, characterized in that: The surface of the lens is provided with the coating film according to any one of claims 4 to 8.
11. A lighting device, comprising a lighting cover, characterized in that: The coating film according to any one of claims 4 to 8 is provided on the surface of the lighting cover.
12. An air conditioner comprising a casing covering a main body, the main body supplying and exhausting air indoors, characterized in that: The surface of the housing is provided with the coating film according to any one of claims 4 to 8.
13. A method for producing a coating film, characterized in that: include: A liquid film forming step, wherein the coating composition according to any one of claims 1 to 3 is applied on a substrate to form a liquid film; and The drying step comprises drying the liquid film.
14. The method for producing a coating film according to claim 13, characterized in that: In the liquid film forming step, a cloth-like object impregnated with the coating composition is fixed to a coater having a surface shaped along the surface of the substrate, and the coater is slid along the surface of the substrate in a state where the cloth-like object is in close contact with the surface of the substrate, thereby forming the liquid film.
Citation Information
Patent Citations
Coating composition, antifouling member, air conditioner and ventilation fan
JP2016089147A
Coating composition, coating method, heat exchanger and air conditioner
CN101583676A